The Influence of Spirituality in the Care of Patients with Advanced Chronic Illnesses and at the End of Life: An Integrative Review - Pérez-Jiménez, José M. (Journal of religion and health, 2026)
Spirituality is a central yet often overlooked component of care, particularly for people facing advanced chronic illness or approaching the end of life. This integrative review examined evidence on how spiritual care influences emotional, existential, and quality of life outcomes, and identified factors that facilitate or hinder its integration into clinical practice. We searched EMBASE, PubMed, Scopus, Web of Science, BvS, Cochrane, and gray literature for peer-reviewed studies published between 2015 and 2025. Inclusion criteria included adults (≥ 18 years) with advanced or terminal illness, as well as quantitative, qualitative, mixed-methods, and review designs, and publications in English, Spanish, or Portuguese. Twenty-four studies met eligibility criteria. Across all settings and diagnoses, higher spiritual well-being was consistently linked to lower anxiety and depression, greater hope and resilience, better health-related quality of life, and greater acceptance of death. Addressing spiritual needs, particularly meaning, belonging, reconciliation, and death preparation, reduced distress and enhanced dignity when integrated into Advance Care Planning. However, heterogeneity in spirituality definitions, limited professional training, and weak institutional support hindered consistent implementation. These findings underscore spirituality as a determinant of health that should be systematically assessed, taught, and incorporated into the care of patients with serious illness. A brief spiritual assessment, structured meaning-centered conversations with family inclusion, and Advance Care Planning that reflects patients’ beliefs and values are recommended.